2019
DOI: 10.1097/brs.0000000000003353
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Convolutional Neural Network With Performance Comparable to Radiologists for Differentiating Between Spinal Schwannoma and Meningioma

Abstract: Study Design. Retrospective analysis of magnetic resonance imaging (MRI). Objective. The aim of this study was to evaluate the performance of our convolutional neural network (CNN) in differentiating between spinal schwannoma and meningioma on MRI. We compared the performance of the CNN and that of two expert radiologists. Summary of Background Data. Preoperative discrimination between spinal schwannomas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…Lastly, the current ANN model is unable to compare or contrast which survey variables were most influential. Even though the constructed ANN model was superior to logistic regression, it still underperformed compared to ANN models applied to complex datasets achieving >80% classification performance . This can be due to the chosen neural network architecture and/or the small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…Lastly, the current ANN model is unable to compare or contrast which survey variables were most influential. Even though the constructed ANN model was superior to logistic regression, it still underperformed compared to ANN models applied to complex datasets achieving >80% classification performance . This can be due to the chosen neural network architecture and/or the small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…This disadvantage is not elaborate along with external validation. Although there are some reports without the external dataset [13,19,23,24], the performance of our DLA should be assessed using an independent external validation dataset to validate our results in the future. Second, this cohort included only patients that were referred to the study center with suspected AIS [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning is a branch of machine learning that has the ability to identify highly complex patterns in large datasets [11]. In particular, convolutional neural networks (CNNs) are designed to learn the features from data through back-propagation by using multiple building blocks, such as convolution layers, pooling layers, and fully-connected layers [12,13]. In the spine field, CNNs have been applied for detection, classification or segmentation of diseases such as differentiation of intradural extramedullary tumors [13] and spinal metastases [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously used in oncological classification tasks with high accuracy. Several studies have demonstrated the ability of transfer learning to work with small datasets using minimal image pre-processing (40)(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%